Karakteristik Habitat dan Keanekaragaman Ikan Air Tawar Sungai Menduk yang Mendapat Pengaruh Penambangan Timah di Kabupaten Bangka - Muslih, Khoirul; Adiwilaga, Enan M; Adiwibowo, Soeryo (Universitas Bangka Belitung, 2014)
Tin mining in Bangka has caused a lot of damage to the environment, including rivers. The damage will affect water quality and aquatic habitat that would threaten the diversity of fish resources. This study aims to determine the effect of tin mining activities on water quality and fish species diversity. The study was conducted in Menduk River during February to May 2013 through fish sampling using gill nets with several mesh sizes. Measurement of water quality parameters was performed and analyzed using Pollution Index (PI) and an index of habitat to investigate the disturbance of habitat due to tin mining. The results showed that the tin mining affects water quality, especially the brightness, turbidity, and TSS. PI based Menduk River was declared contaminated with habitat conditions upstream in heavy interference conditions. Lowest diversity index fish in upstream and overall found 21 species of fish from 10 families in the River Menduk.